Pre-trial Detention Challenges in Sweden and Ukraine (Journal of Legal Studies, 2024)
This article conducts a comparative analysis of pre-trial detention challenges in Ukraine and Sweden, highlighting common issues and distinctive features. Both countries face non-compliance with international standards in their remand policies, with legislative problems serving as a focal point. Recent legislative efforts in Ukraine and Sweden have addressed some issues, but significant challenges persist, requiring comprehensive solutions. The legislative disparities between the two nations manifest in the technical nature of Ukraine's problems and Sweden's more systemic issues. A unique challenge faced solely by Sweden is the disproportionately high number of foreigners in pre-trial detention, highlighting discriminatory legal regulations. Procedural hurdles vary, with Sweden grappling with the lack of specificity in prosecutors' grounds for restrictions, while Ukraine faces a formalistic approach to remand extensions. Long-term pre-trial detention is identified as a shared concern, attributed to systemic principles in Sweden and technical procedure problems.